Self-limiting electropolymerization of ultrathin, pinhole-free poly(phenylene oxide) films on carbon nanosheets. (July 2015) - Deheryan, S.; Cott, D.J.; Muller, R.; Timmermans, M.; Heyns, M.; Vereecken, P.M.
Abstract: Poly(phenylene oxide) (PPO) is an electronically insulating, solid polymer film which can be prepared via electropolymerization of phenol on electronically conductive surfaces. The self-limiting nature of this reaction allows the formation of pinhole-free films with nanometer thickness on high aspect ratio micro- and nano-structured substrates. In this work, we investigated the electrodeposition of PPO on carbon nanosheets (CNS). The highly corrugated CNS morphology makes a perfect model substrate to study the conformal electrodeposition of PPO films for advanced energy storage devices based on three-dimensional large-area surfaces. Uniform PPO films of about 8 nm were successfully coated over CNS layers with area enhancements of over 200×. The films uniformly covered the CNS petals and were electronically insulating as confirmed from cyclic voltammetry tests in redox electrolyte solutions. These thin conformal PPO films are of interest for blockage of electronic leakage in supercapacitor applications or even as ion conducting buffer layers in lithium ion batteries.